Bootstrap geologist : my life in science - Shinn, Eugene A. (University Press of Florida, 2013)
A memoir by Eugene Shinn of his life in geological field science. In this book, he shares the highs and lows of his remarkable life. Taking readers around the globe as well as below the ocean, he recounts the painstaking process of data gathering that can lead to paradigm-breaking discoveries. He emphasizes the importance of field science and pointedly addresses the use and abuse of scientific research and the emergence of market-funded research.